Pengaruh Karakteristik Individu Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Smp Negeri Di Kecamatan Kumpe Ulu Kabupaten Muaro Jambi - Redi Indra Yudha (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
The purpose of this research is to describe and relationships far the effect of individual characteristics and learning motivation on student learning outcomes Junior High School in the district of Ulu Kumpe Muaro Jambi. The population in this research were 860 people with the withdrawal by proportional random sampling, the samples obtained amounted to 273. Based on the results, it can be concluded that student learning will feel confident or not in their ability to understand the material given through the adjustment and motivation to learn that is within each student. That is, students who have character and a high learning motivation will get results and better learning achievement.